Animal Care and Ethics in Contemporary Religious Debates - Peter Ottuh; Onos Godwin Idjakpo (Universitas Negeri Makassar, 2021)
Can religious worldview help humans respect non-human-animals, and achieve a better, more balanced environment? Since Lynn White wrote a damming essay against the Judeo-Christian religion, the answer to the question among most environmental ethicists has often beenon the negative. Lynn White had accused the Western Judeo-Christian worldview as been anthropocentric. Anthropocentrism is the worldview that places humanity at the center of all moral concern, hence, such a worldview enhances the conditions for human exploitation of non-human animals. The Judeo-Christian worldview specifically holds that the Universe was created and fine-tuned for the creation of the human species in particular. On a personal level, this ideology drives the fragile Human ego to think that the God of the Universe created everything on earth for human consumption and domination. Hence, many scholars believe that such a worldview is seen and dominant among most religions across the world. This paper attempt to join the contemporary debates on religious worldview and Animal ethics.Against the popular notion, this paper argues that mostReligious traditions have often been the primary movers of a compassionate engagement with other lives. Thus, religious persons can still respect and conserve animals irrespective of their religion.